Pengaruh Variasi Volume Pengenceran Bakteri Bacillus Subtilis Terhadap Sifat Fisik Beton Pada Lingkungan Sulfat - Suziela Saila; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Concrete is a material that generally becomes a necessity as a support for infrastructure. Concrete has various advantages so it is chosen in the field of construction. During the construction, several weakness were found w in concrete that can make cracks and cause performance in concrete being decreased. To overcome this issue, cracks on concrete can be self-recovered, called self healing concrete. In this study, bacteria Baciluus Subtilis was used as a medium that can restore cracks in concrete. In this study, ingredients added with bacillus subtilis bacteria with a concentration of 105 cells / 20 ml, 105 cells / 25 ml, and 105 cells / 30 ml of 25 ml in each casting were then treated in sulfate solution and studied physical properties. Normal concrete is compared with bacterial concrete with different concentrations at 28 and 56 days of treatment in water sulphate. . Concrete testing performed is workability, porosity, and shrinkage. The results of this study indicate that the slump in sulfur bacteria 105 cells / 20 ml is 9.50 cm, porosity in the concrete bacteria sulfate 105 cells / 20 ml is lower than the other types of concrete with a value of 13.54%. Shrinkage on concrete sulfate bacteria 105 cells / 20 ml is lower than other types of concrete with shrinkage of 0.071 mm or 71 μm. So that it can be concluded that the bacterial sulfate 105 cells / 20 ml concrete is the most optimum with added bacterial ingredients in the sulfate environment.Keywords: Concrete, Bacillus subtilis bacteria, physical properties, sulfate, concentration